Single-center Experience of Histopathological Spectrum and Treatment Profile in Adolescent-onset Nephrotic Syndrome in India - Pradhan, Subal Kumar; Satpathy, Saroj Kumar; Bhat, Shreesh; Krishnamoorthy, Akhil (Journal of Pediatric Nephrology, 2018)
Introduction: Guidelines suggest a biopsy-tailored treatment rather than glucocorticoids as initial therapy for adolescent-onset nephrotic syndrome (NS) as minimal change disease is more common in younger children. There is a paucity of data regarding the clinical course and renal histopathological findings in this population. This study analyzed the clinical course and histological spectrum of adolescent-onset NS. Materials and Methods: In this retrospective study, we evaluated the medical records of patients with adolescent-onset NS who received treatment at the Department of Pediatrics, SVPPGIP & SCB Medical College, Cuttack, Orissa, India, between January 2010 and January 2017. Patients with congenital, infantile, childhood-onset, and secondary causes of NS were excluded. All children were treated as per the Indian Society of Pediatric Nephrology (ISPN) protocol. Results: The data of 48 adolescents were analyzed. The median age at onset of disease was 12 years (range: 10-14 years), and 68.75% (33/48) of the patients were males. Steroid-dependent NS (SDNS, 43.7%, 21/48) was the most common clinical course followed by frequently relapsing NS (FRNS, 29.1%, 14/48). Prednisolone with tacrolimus (37.5%, 18/48) and mycophenolatemofetil (35.4%, 17/48) were the most commonly used treatments. Biopsy results showed that minimal change disease (MCD) was the most common histopathological subtype (37.5%, 18/48) closely followed by focal segmental glomerulosclerosis (FSGS, 31.2%, 15/48). Most of the cases responded to a combination of prednisolone with either MMF, cyclophosphamide, or tacrolimus (23%). Conclusions: The most common underlying cause of adolescent-onset nephrotic syndrome as assessed histopathologically is MCD, closely followed by FSGS with most of the cases responding to a combination of prednisolone with either mycophenolatemofetil, cyclophosphamide or tacrolimus. Keywords: Adolescent-onset nephrotic syndrome; Minimal change disease; Focal segmental glomerulosclerosis; Steroid; Histopathology.